Endovascular Repair of Mycotic Aneurysm of the Descending Thoracic Aorta: Diagnostic and Therapeutic Dilemmas—Two Case Reports with 1-Year Follow-Up - Marjanovic, Ivan; Sarac, Momir; Tomic, Aleksandar; Bezmarevic, Mihailo (The Thoracic and Cardiovascular Surgeon, 2013)
A mycotic aneurysm of the thoracic aorta is a rare diagnosis with high mortality. We present two cases of endovascular reconstruction of mycotic descending thoracic aorta. Specific or nonspecific bacterial or other infectious agent in serial samples of blood, urine, cerebrospinal fluid, and pleural puncture was not detected in the first case, but we found in sputum sample Mycobacterium tuberculosis in the second patient. We empirically began by administering broad-spectrum intravenous antibiotics in the first case, with preoperative antibiotic prophylaxis and antituberculotic drugs therapy in the second case, and continued with the same medication for 4 months after endovascular repair. Control computed tomographic scans 6 months after reconstruction showed no endoleak in both patients. Repair of mycotic descending thoracic aortic aneurysms by endoluminal stent graft is reasonable alternative to open surgical intervention. A broad-spectrum antibiotic therapy has a high significance in the treatment of patients with mycotic aneurysm.
Keywords: endovascular graft; descending thoracic aorta; mycotic aneurysm; pathogens; antibiotics